Factors contributing to infidelity in marriage within Asian countries a systematic review of literature - Mah, Yong Xin; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2020)
Infidelity in the marriage is one of the issues currently we have in this era. We cannot deny it is happening in this twenty-first century. Most common issue related to infidelity is sexual intercourse with the third partner beside the legal wife. Extramarital sex is considered as betray toward the marriage. It can be described like having sex outside the marriage. There are some factors can be connected to the infidelity issue such as marital jealousy, lack of paternal care in children, discomfort in marriage, and dissatisfy in sexual experience. This fault is no longer labels for men only but also to the women. This is a systematic review paper to explore and discover about what are the factors contribute to the extramarital sex. The journals for review are selected from the Asian region, and a total of 10 journals from different countries including China, Pakistan, Bangladesh, India and Vietnam.